DIALEKTIKA TEORI KRITIS MAZHAB FRANKFURT DAN SOSIOLOGI PENGETAHUAN - Andy Dermawan (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
The existence of Critical Theory which inspired by Marx, actually directed to the reversion of human’s value and dignity as a whole. Hence, it’s properly, more emancipatoric. As important note here, that in spite of Critical Theory existed from Marx’s spirit, but not meant to adopt and dogmatize from him, just taking his great and basic thought, i.e. setting human free from the shackle of his own creation. In fact, the central issue of the Sociology of Knowledge is that the effort in disclosing sociological sources in all form of knowledge, thought and awareness of whole human’s mental activities. This article aims to present Critical Theory of Frankfurt Sect and the Sociology of Knowledge in sociological perspective, in order to understand it’s scientific geneology and epistemology. And also observing the possibility of developing scientific sociology in the future. Keberadaan Teori Kritis yang terinspirasi Marx, sebenarnya diarahkan untuk pengembalian nilai manusia dan martabat secara keseluruhan. Oleh karena itu, lebih emansipatoris. Sebagai catatan penting, meskipun Teori Kritis ada dalam semangat Marx, tetapi tidak dimaksudkan untuk mengadopsi dan dogmatik darinya. Akan tetapi hanya mengambil dasar pemikiran, yaitu pengaturan manusia yang bebas dari belenggu ciptaan sendiri. Bahkan, isu sentral dalam Sosiologi Pengetahuan adalah upaya pengungkapan sumber sosiologis dalam semua bentuk pengetahuan, pemikiran dan kesadaran aktivitas mental seluruh manusia. Artikel ini bertujuan untuk menyajikan Teori Kritis Frankfurt dan Sosiologi Pengetahuan dalam perspektif sosiologis, untuk memahami silsilah ilmiah dan epistemologi. Serta mengamati kemungkinan mengembangkan sosiologi ilmiah di masa depan.